2007
DOI: 10.2527/jas.2006-087
|View full text |Cite
|
Sign up to set email alerts
|

Lipogenesis and stearoyl-CoA desaturase gene expression and enzyme activity in adipose tissue of short- and long-fed Angus and Wagyu steers fed corn- or hay-based diets

Abstract: Angus and Wagyu steers consuming high-roughage diets exhibit large differences in adipose tissue fatty acid composition, but there are no differences in terminal measures of stearoyl-CoA desaturase (SCD) activity or gene expression. Also, adipose tissue lipids of cattle fed corn-based diets have greater MUFA:SFA ratios than cattle fed hay-based diets. We hypothesized that any changes in SCD gene expression and activity would precede similar changes in adipose tissue lipogenesis between short- and long-fed endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 17 publications
3
83
0
3
Order By: Relevance
“…Chung et al (2007) also observed greater adipocyte density (more adipocytes/100 g tissue) in SC and IM AT in corn-fed long-fed (from 8 to 24 months of age) Angus steers as compared with corn-fed short-fed (from 8 to 16 months of age) steers, suggesting the emergence of newly formed adipocytes or a population of small cells in the AT of steers fed non-structural carbohydrate for a longer period. Adipocyte proliferation could, as well, be related to mature adipocyte size, as suggested by studies showing that on reaching a critical volume rat adipocytes secrete factors that recruit new adipocytes (Marques et al, 1998), increasing tissue storage capacity.…”
Section: Marbling and Adipositymentioning
confidence: 70%
See 1 more Smart Citation
“…Chung et al (2007) also observed greater adipocyte density (more adipocytes/100 g tissue) in SC and IM AT in corn-fed long-fed (from 8 to 24 months of age) Angus steers as compared with corn-fed short-fed (from 8 to 16 months of age) steers, suggesting the emergence of newly formed adipocytes or a population of small cells in the AT of steers fed non-structural carbohydrate for a longer period. Adipocyte proliferation could, as well, be related to mature adipocyte size, as suggested by studies showing that on reaching a critical volume rat adipocytes secrete factors that recruit new adipocytes (Marques et al, 1998), increasing tissue storage capacity.…”
Section: Marbling and Adipositymentioning
confidence: 70%
“…For instance, Chung et al (2007) observed that SC fat thickness and marbling scores increased over time in corn and hay-fed steers and showed that long-fed (16M), grain-fed cattle produced higher quality carcasses with softer fat than short-fed (8M), grain-fed cattle, while Moura et al (2013) reported that steers fed a high-fat diet (2.7% v. 7.1%) resulted in downregulation of proteins involved in preadipocyte growth arrest and concluded that preadipocyte proliferation was favoured over differentiation and may have been more intense in both the visceral and SC ATs in steers fed with high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, the 0% WDGS steers needed to generate more MUFA from SFA because less PUFA was available in the plasma to incorporate in the organelle membrane. The other possibility is that the 50% WDGS diet (high in PUFA) may have suppressed the stearoylCoA desaturase gene, which is the gene that encodes for delta-9-desaturase (Chung et al 2007).…”
Section: Sr Membrane Fatty Acidsmentioning
confidence: 99%
“…El grupo PB fue el que presentó los menores pesos de canal caliente en relación al grupo CA. Al tener menor contenido de ácidos grasos mono-insaturados (principal- mente ácido oleico, C18:1, cis-9) sugiere que podría haber una depresión de la actividad de las desaturasas (Chung et al, 2007). Baeza et al (2012) encontraron efectos significativos de los polimorfismos SRPR sobre la actividad de las desaturasas en novillos Brangus alimentados a pasto, destacando la importancia de los procesos de señalización celular para el transporte y la activación temprana de la proteína, y un papel de apoyo para estos mecanismos en la variabilidad de la composición y perfil de ácidos grasos en la carne bovina.…”
Section: Resultados Y Discusiónunclassified